Answer:
![x = -3 + 2\sqrt2 \ , \ x = -3 - 2\sqrt2](https://tex.z-dn.net/?f=x%20%3D%20-3%20%2B%202%5Csqrt2%20%20%5C%20%2C%20%5C%20x%20%3D%20-3%20-%202%5Csqrt2)
Step-by-step explanation:
x² + 6x + 1 = 0
a = 1 , b = 6 , c = 1
![x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\\\\x = \frac{-6 \pm \sqrt{36-4}}{2}\\\\x=\frac{-6 \pm \sqrt{32}}{2}\\\\x= \frac{-6 \pm \sqrt{16 \times 2}}{2}\\\\x = \frac{-6 +4\sqrt2 }{2}\\\\x = -3 + 2\sqrt2 \ , \ x = -3 - 2\sqrt2](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E2%20-%204ac%7D%7D%7B2a%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B-6%20%5Cpm%20%5Csqrt%7B36-4%7D%7D%7B2%7D%5C%5C%5C%5Cx%3D%5Cfrac%7B-6%20%5Cpm%20%5Csqrt%7B32%7D%7D%7B2%7D%5C%5C%5C%5Cx%3D%20%5Cfrac%7B-6%20%5Cpm%20%5Csqrt%7B16%20%5Ctimes%202%7D%7D%7B2%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B-6%20%2B4%5Csqrt2%20%7D%7B2%7D%5C%5C%5C%5Cx%20%3D%20-3%20%2B%202%5Csqrt2%20%20%5C%20%2C%20%5C%20x%20%3D%20-3%20-%202%5Csqrt2)
Answer:
6
h
+
2
y
+
4 is your answer
Step-by-step explanation:
Hope this helps! :)
<span>3rd angle of a triangle = 180 -(44 + 72) = 180 - 116 = 64
answer
</span><span>3rd angle of a triangle = 64 degrees</span>
Answer:
3039007
Step-by-step explanation:
V= 13
Substitue (v) for 13
7253(8*4(13))
Go by the rules be PEMDAS
First you the parentheses
4 times 13= 52
52 times 8= 416
Now you just multiply the two numbers
416 times 7253= 3039007